2017
DOI: 10.4236/oalib.1104246
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Suspected Malaria Outbreak in Sokoto State, Nigeria, 2016

Abstract: Background: Malaria, a vector borne disease that contributes to the 17 percent of the global burden of infectious diseases, is preventable, treatable and completely curable. The disease is endemic in Nigeria, staggering at 27 percent prevalence and contributes up to 29 percent of global burden of the disease. It contributes to the high child mortality in Nigeria, attributed 30 percent of under five deaths. In October 2016, WHO team in Nigeria in collaboration with Nigerian Centre for Disease Control investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This outcome is consistent with the findings in a study conducted in Kano and Sokoto states in 2016 which showed that respondents had good levels of knowledge and attitudes regarding malaria transmission, symptoms, and prevention [11] [14]. The limitation of this study was that those interviewed to assess their knowledge of malaria preventive measures were not necessary patients who received treatment at the health facility during the malaria outbreak.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This outcome is consistent with the findings in a study conducted in Kano and Sokoto states in 2016 which showed that respondents had good levels of knowledge and attitudes regarding malaria transmission, symptoms, and prevention [11] [14]. The limitation of this study was that those interviewed to assess their knowledge of malaria preventive measures were not necessary patients who received treatment at the health facility during the malaria outbreak.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, 69% of pregnant women lack access to the recommended minimum of three doses of intermittent preventive treatment in pregnancy (IPTp) during antenatal visits[3] [4] [6][7] [8][9]. Thus, for country programmes to achieve malaria elimination, there is need for adherence to the critical preventive measures against malaria which include the use of long-lasting insecticide-treated nets (LLINs), indoor residual spraying (IRS), use of preventive medicines in the most vulnerable groups (IPTp, IPTi and SMC) and improve access to these critical tools[10] [11].…”
mentioning
confidence: 99%